Perlindungan konsumen di pasar abad ke-21 melalui lensa hukum, empiris, dan islam - Sigli, Syawalia Novita (Maliki Interdisciplinary Journal, 2025)
This scientific article examines consumer protection in the 21st-century marketplace through the lenses of positive law, empirical analysis, and Islamic perspective. Amid globalization and digital advancements, consumers face risks such as online fraud, lack of transparency, and low awareness of their rights. Law No. 8 of 1999 serves as Indonesia’s legal foundation for consumer protection, yet its implementation remains limited. Empirical studies indicate that strong regulations enhance consumer trust and satisfaction. Meanwhile, Islamic principles of justice, honesty, and prohibition of exploitation offer ethical foundations for modern business practices. This article aims to provide a comprehensive understanding and promote synergy between national law and religious values to establish a fair and sustainable consumer protection system.